Influence of own weight on dynamic analysis of a pre-stretched plate-strip containing a circular hole under bending load - Yesil, Ulku Babuscu (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
This paper investigates the effect of own weight on the dynamic analysis of a pre-stretched composite plate-strip containing a circular hole subjected to bending load. The combined effect of body forces (weight) and surface forces (pre-stretching load) on the plate-strip with a hole is considered as the initial stresses determined within the linear theory of elasticity. The effects of these initial stresses on the natural and forced vibrations around the hole within a plate-strip under additional bending load are investigated in the framework of the Three-Dimensional Linearized Theory of Elasticity (TDLTE) under the plane strain state, and the solutions of the considered boundary value problems are solved numerically by using the finite elements method. This paper shows that the influence of the plate's own weight has an important role on the dynamic analysis around the circular hole within a plate-strip.
Keywords: Own weight; initial stress; dynamic analysis; circular hole; finite element method; RECTANGULAR COMPOSITE PLATE; DEAD LOADS; VIBRATION; Engineering